Analysis of Method Performance for Quantitative Assessment of Listeria monocytogenes in Queso Fresco Cheese - Neha Singh; Ravinder Reddy; Karina Hettwer; Kirstin Frost; Matthew Kmet; Steffen Uhlig (Journal of Food Protection)
A Proficiency Test (PT) was conducted for Food Emergency Response Network (FERN) laboratories for quantitative assessment of Listeria monocytogenes (L. monocytogenes) in queso fresco cheese. The Moffett Proficiency Test Laboratory: MPTL (organizer) prepared test samples for each participating laboratory with 10 CFU/g of L. monocytogenes. Statistical analysis was conducted to analyze test sample preparation and evaluate the performance of the quantitative method by utilizing participant’s data. Although individually inoculated, the samples were considered replicates based on the standard deviation values obtained from the Q/Hampel method. A similar observation was noted on pre- and postshipment data, which permitted a combined analysis as per Q/Hampel and ISO 5725-2 methods. Based on the results, it can be summarized that MPTL prepared homogenized and stable samples for L. monocytogenes enumeration in cheese. The participant results indicated that the repeatability of standard deviation, which reflects the scatter of results within a laboratory (participant), was mainly driven by the MPN procedure. Out of forty reported results from twenty laboratories, 85% were satisfactory. A few laboratories reported different MPN results (2.5% unsatisfactory, and 12.5% warning) indicating a lack of understanding in handling the MPN dilutions. Since BAM MPN-based method performance data for L. monocytogenes is not widely available in the literature, more PT events like these can help generate quantitative data for the evaluation of the MPN method.